2021
DOI: 10.1017/s1368980021001567
|View full text |Cite
|
Sign up to set email alerts
|

“My coupons are like gold”: experiences and perceived outcomes of low-income adults participating in the British Columbia Farmers’ Market Nutrition Coupon Program

Abstract: Objective: The British Columbia Farmers’ Market Nutrition Coupon Program (FMNCP) provides low-income households with coupons valued at $21/week for 16 weeks to purchase healthy foods in farmers’ markets. Our objective was to explore FMNCP participants’ experiences of accessing nutritious foods, and perceived program outcomes. Design: This study used qualitative description methodology. Semi-structured interviews were conducted with FMNCP participants during the 2019 farmers’ market seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Since participants' options of where to redeem coupons were influenced by seasonality (coupons were redeemable at the farm after the FM had closed for the season), it is not possible to discern whether the coupon redemption location (farm v. FM) was the sole driver of this outcome. Past research with FM coupon interventions also indicates that FM vouchers can increase feelings of autonomy and dignity among consumers of low income, while supporting social connections and fostering a sense of community (49) . In the future, researchers could investigate whether vouchers for local farms have similar impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since participants' options of where to redeem coupons were influenced by seasonality (coupons were redeemable at the farm after the FM had closed for the season), it is not possible to discern whether the coupon redemption location (farm v. FM) was the sole driver of this outcome. Past research with FM coupon interventions also indicates that FM vouchers can increase feelings of autonomy and dignity among consumers of low income, while supporting social connections and fostering a sense of community (49) . In the future, researchers could investigate whether vouchers for local farms have similar impacts.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in redemption rate suggests that the timing and/or parking barriers may be barriers to shopping at FM for vulnerable populations. Research on FM with similar populations has also found transportation and timing/market hours to be key factors that influence FM utilisation (48,49) . It may be easier to arrange transportation to a local farm, which has more open hours than the weekly FM.…”
Section: Discussionmentioning
confidence: 99%
“…Equity issues can compromise farmers' markets' ability to address food access (Caron-Roy et al, 2021;Klassen & Murphy, 2020;Queirolo, 2019). The high cost associated with organic produce or fruits and vegetables grown by small, family-owned farms is a barrier to low-income families.…”
Section: The Scarbto Mrkt Bucks Initiativementioning
confidence: 99%
“…These incentives have effectively motivated participants to purchase from farmers' markets by "stretching" their food assistance benefits, mitigating the cost of produce, and decreasing overall worry about the cost of food [33,42]. Some of these programs also offer nutrition education classes, educational materials, and other activities [45][46][47]. Many of these incentive programs have succeeded in bringing new, low-income consumers to farmers' markets who otherwise would have not shopped there [32,41,48].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of documented barriers, researchers have found that farmers' market patronage along with incentive program participation is associated with increased fruit and vegetable consumption [41][42][43]46,[48][49][50][51][52][53]; the temporary alleviation of food insecurity [50]; an increased sense of financial autonomy and dignity [41,47]; an increased sense of social and community connection [29,41,47,50]; and increased nutritional knowledge and skills for both adults and children [29,47,50]. These benefits seem to increase along with the frequency of farmers' market patronage.…”
Section: Introductionmentioning
confidence: 99%